2014
DOI: 10.2337/dc13-2990
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lowering the Glycemic Load With Canola Oil on Glycemic Control and Cardiovascular Risk Factors: A Randomized Controlled Trial

Abstract: OBJECTIVEDespite their independent cardiovascular disease (CVD) advantages, effects of a-linolenic acid (ALA), monounsaturated fatty acid (MUFA), and low-glycemicload (GL) diets have not been assessed in combination. We therefore determined the combined effect of ALA, MUFA, and low GL on glycemic control and CVD risk factors in type 2 diabetes. RESEARCH DESIGN AND METHODSThe study was a parallel design, randomized trial wherein each 3-month treatment was conducted in a Canadian academic center between March 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…This is also supported by the favorable glycemic effects shown for the MUFA-rich canola oil (26). The influence of the degree of fat unsaturation on postprandial glucose and insulin responses has been evaluated in healthy people (16,27) and patients with type 2 diabetes (17) with no univocal results, with the inconsistencies mainly related to differences in the experimental design.…”
Section: Resultsmentioning
confidence: 76%
“…This is also supported by the favorable glycemic effects shown for the MUFA-rich canola oil (26). The influence of the degree of fat unsaturation on postprandial glucose and insulin responses has been evaluated in healthy people (16,27) and patients with type 2 diabetes (17) with no univocal results, with the inconsistencies mainly related to differences in the experimental design.…”
Section: Resultsmentioning
confidence: 76%
“…Replacing saturated fat with monounsaturated or polyunsaturated fat reduces low-density lipoprotein cholesterol (LDL-C) and preserves HDL-C (109). Further, canola oil, as part of a low-glycemic index diet, improves glycemic control and blood lipids in type 2 diabetes (138). Trans -fatty acids increase CHD risk compared with other macronutrients, with strong evidence of adverse effects of small amounts of trans -fats on lipids (109,139) and CVD risk (140,141).…”
Section: Macronutrients Foods and Cvd Risk Factorsmentioning
confidence: 99%
“…Recent animals trials confirm this specific propriety, proving that canola oil has a better effect on pressure, compared to other vegetables oils [50]. Moreover, it has been demonstrated that the supplementation of canola oil, rich of MUFA and α-linolenic acid (ALA), improve glycemic control in diabetic patients with high systolic blood pressure [51].…”
Section: Action On Blood Pressure Glycemic Control and Inflammatorymentioning
confidence: 82%